1969
DOI: 10.1136/jcp.22.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glandular polypi of the uterine cervix associated with contraceptive pills: Pathology and pathogenesis

Abstract: Fifteen cases of aberrant polypoidal glandular hyperplasia of the cervix are described. The lesion was found in five pregnant patients. The remaining 10 patients had taken contraceptive pills over a considerable period of time.The lesion while histologically bizarre is benign, the changes being to a great extent cytoplasmic and not nuclear. It is suggested that it is formed by the influence of steroids on a cervix which is already pathological. It is further suggested that two changes are essential before ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Initial reports suggested strong association with oral contraceptive use and pregnancy (1)(2)(3)(4)17); however, subsequent studies revealed lack of such clinical history in at least 50% of patients (18,19). Macroscopically it commonly presents as a polypoid lesion, often with surface erosions, or it may be …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Initial reports suggested strong association with oral contraceptive use and pregnancy (1)(2)(3)(4)17); however, subsequent studies revealed lack of such clinical history in at least 50% of patients (18,19). Macroscopically it commonly presents as a polypoid lesion, often with surface erosions, or it may be …”
Section: Discussionmentioning
confidence: 95%
“…Although its potential malignant nature was raised in early publications, subsequent papers confirmed a benign clinical course and association with pregnancy and oral contraceptives in at least a large proportion of cases (2)(3)(4). Grossly, MGH commonly presents as a polypoid lesion with surface erosion.…”
mentioning
confidence: 95%
“…Most cases represent benign endocervical MGH and can be readily diagnosed as such if it presents in the right clinical context and shows characteristic microscopic features of the lesion. That is, most patients with MGH are young -within their reproductive years, and up to half of them report oral contraceptive use or concurrent pregnancy [1,[17][18][19][20][21][22][23]. Typical morphological features of MGH include tightly packed, small glands with scant intervening stroma; bland, cuboidal, or low columnar mucinous glandular epithelium; and rare to absent mitotic figures [2].…”
Section: Discussionmentioning
confidence: 99%
“…The normal changes of the cervix during pregnancy include softening, cyanosis, hypertrophy, increased vascularity and hyperplasia of the endocervical glands, including Arias‐Stella change 12–15 . Microglandular hyperplasia of the cervix may appear as a polypoid or nodular excrescence and has been reported in pregnancy 13,16 . Biopsy is necessary to provide the histological diagnosis for a cervical lesion, but if a lesion is discovered during labour rapid diagnosis may not be possible.…”
Section: Discussionmentioning
confidence: 99%